Improving Soil Quality by Using Oil Palm Solid Waste Biochar - Darmawan Darmawan; Sari Handani; Ikhsanul Adli (AGRITROPICA : Journal of Agricultural Sciences, 2021)
Solid waste and land degradation are two main problem faced by oil palm plantation in mineral soils. In order to get rid of these difficulties, a field experiment has conducted at re-planting stage of oil palm in PT. Tidar Kerinci Agung plantation. The objective of this study is to examine the potentiality of biochar made from empty bunch of oil palm on soil quality. Fifteen plots of 100 square meters were applied with the dose of 0.0, 2.5, 5.0, 7.5 and 10.0 Mg/ha biochar, respectively. The results show the treatment increase soil organic matter, total pore space, water holding capacity and cation exchange capacity. On the other hand, soil bulk density found decrease significantly along with the treatment. These results indicated that application of biochar might be a better choice for sustainable oil palm plantation in mineral soil.